Double metal cyanides as efficient solid acid catalysts for synthesis of beta-amino alcohols under solvent-free conditions - Saikia, Lakshi; Satyarthi, J. K.; Gonnade, Rajesh G.; Srinivas, Darbha; Ratnasamy, P. (Catalysis Letters, 2008)
A novel application of Fe-Zn double metal cyanide complexes as solid, acid catalysts for regioselective synthesis of beta-amino alcohols under solvent-free conditions via ring-opening of epoxides with amines is reported for the first time. The conversion of epoxides to beta-amino alcohols is nearly 100%. In the reaction with styrene oxide, regioselective beta-amino alcohol formation is higher with aromatic than with aliphatic amines. Strong Lewis acidic Zn(2+) ions in the catalyst are probably the active sites in this reaction.
Keywords: beta-Amino alcohols; double metal cyanide (DMC); regioselective ring-opening of epoxides; Single crystal x-ray structure; solid Lewis-acid catalyst

Sesquiterpene lactone, a potent drug molecule from artemisia pallens wall with anti-inflammatory activity - Ruikar, Anjali D.; Misar, Ashwini V.; Jadhav, Ravindra B.; Rojatkar, Supada R.; Mujumdar, Arvind M.; Puranik, Vedavati G.; Deshpande, Nirmala R. (Arzneimittel-Forschung-Drug Research, 2011)
The present study was carried out to investigate the anti-inflammatory activities of bioactive secondary metabolites of Artemisia pallens Wall, an aromatic herb from family Asteraceae. The results provide evidence for the topical anti-inflammatory properties of Artemisia pallens Wall. The compounds were isolated from the acetone extract of the plant material. The isolates were tested on Swiss albino mice using 12-O-tetradecanoyl phorbol-13-acetate (TPA) induced ear edema. One of the molecules from the extract indicated potent anti-inflammatory activity equivalent to indometacin (CAS 53-86-1). Elucidation of the molecular structures by single crystal x-ray diffraction studies revealed the conformational differences that the six membered rings in both the molecules are at an angle of 28.79 degrees. Presence of hydroxy function for compound 2 may be responsible for higher potency.
Keywords: Anti-inflammatory activity; Artemisia pollens; Asteraceae; Mice; Single crystal x-ray structure

Cyanuric-chloride-mediated synthesis of 2-Aryl-3-tert-butoxycarbonyl-thiazolidine-4-carboxylic acid anilides: mechanistic, X-ray crystal structures and cytotoxicity studies - Jagtap, Rohidas M.; Shaikh, Samir R.; Gonnade, Rajesh G.; Raheem, Shabnam; Rizvi, Masood A.; Pardeshi, Satish K. (ChemistrySelect, 2019)
The `2R,4R'-2-aryl thiazolidine-4-carboxylic acid anilides (ATCAAs) were synthesized using cyanuric chloride (CC) as a clean and substoichiometric acid-amine coupling agent under optimized reaction conditions. The diesterphenol intermediate based mechanism is proposed and supported by spectral characterization of the intermediate. The single crystal X-ray structures of acid substrate (2R,4R)-3-(tert-butoxycarbonyl)-2-(2-methoxyphenyl)thiazolidine-4-carbox ylic acid (3 a) and anilides (R)-tert-butyl 4-(2-fluorophenylcarbamoyl)thiazolidine-3-carboxylate (4 b), (2R,4R)-tert-butyl 2-(2,6-dichlorophenyl)-4-(m-tolylcarbamoyl)thiazolidine-3-carboxylate (6 b) confirmed the formation of chiral anilides. The synthesized library of anilides [(R)-tert-butyl 4-Aryl thiazolidine-3-carboxylate and (2R,4R)-tert-butyl 2-Aryl-4-Aryl thiazolidine-3-carboxylate] 4 a-6 f was screened for their in vitro anti cancer, neuronal and neuroprotective studies. The anilides 4 b, 4 g, 5 d, 5 h, 6 c and 6 f (where the aryl=2-fluorophenylcarbamoyl, 4-chlorophenylcarbamoyl, 2-methoxyphenyl, 2,5-dichlorophenylcarbamoyl, 2,6-dichlorophenyl, 4-chlorophenylcarbamoyl respectively)were found to be less cytotoxic towards N2 A, SHSY-5Y neuronal cell lines in their differentiated and undifferentiated forms, and also exhibited dose dependant anti-inflammatory properties for a possible identification towards neurodegenerative and inflammatory disorders.
Keywords: Acid-amine coupling; Cyanuric chloride; Cytotoxicity; Mechanistic investigations; Single crystal x-ray structure